Pseudosolvent Intercalator of Chitin: Self‐Exfoliating into Sub‐1 nm Thick Nanofibrils for Multifunctional Chitinous Materials. Issue 10 (3rd February 2021) - Yang, Kaihua; Zhou, Youshuang; Wang, Zengbing; Li, Mingjie; Shi, Dean; Wang, Xianbao; Jiang, Tao; Zhang, Qunchao; Ding, Beibei; You, Jun
Abstract: Traditionally, energy‐intensive and time‐consuming postmechanical disintegration processes are inevitable in extracting biopolymer nanofibrils from natural materials and thereby hinder their practical applications. Herein, a new, convenient, scalable, and energy‐efficient method for exfoliating nanofibrils (ChNFs) from various chitin sources via pseudosolvent‐assisted intercalation process is proposed. These self‐exfoliated ChNFs possess controllable thickness from 2.2 to 0.8 nm, average diameter of 4–5 nm, high aspect ratio up to 10 3 and customized surface chemistries. Particularly, compared with elementary nanofibrils, ChNFs with few molecular layers thick exhibit greater potential to construct high‐performance structural materials, e.g., ductile nanopapers with large elongation up to 70.1% and toughness as high as 30.2 MJ m −3, as well as soft hydrogels with typical nonlinear elasticity mimicking that of human‐skin. The proposed self‐exfoliation concept with unique advantages in the combination of high yield, energy efficiency, scalable productivity, less equipment requirements, and mild conditions opens up a door to extract biopolymer nanofibrils on an industrial scale. Moreover, the present modular ChNFs exfoliation will facilitate researchers to study the effect of thickness on the properties of nanofibrils and provide more insight into the structure–function relationship of biopolymer‐based materials. Abstract : A pseudosolvent‐assisted intercalation process that can circumvent strong mechanical disintegration is developed to extract chitin nanofibrils. Having controllable thickness down to 0.8 nm, average diameter of 4–5 nm, and high aspect ratio up to 10 3, these ribbon‐like nanofibrils can act as new building blocks to fabricate high‐performance structural materials, being applicable in optics, wearable electronics, and energy devices.